THEORY OF TORSIONAL VIBRATIONS OF GROOVED CYLINDERS - Lastochkin, Pavel; Parpieva, Nilufar; Kayumov, Juramirza; Parpiyev, Doniyor (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The article addresses one of the most pressing challenges in the modern textile industry - the need to increase the speed of spinning equipment while simultaneously enhancing yarn quality. The key element determining yarn quality is the spinning machine’s drafting device, particularly its corrugated cylinders. Existing studies indicate that the primary causes of yarn unevenness and breakage lie in imperfections of the drafting device, which are associated with geometric errors in the manufacturing of corrugated cylinders, their dynamic characteristics, and torsional vibrations during operation. The problem of joining corrugated cylinders is especially critical, as traditional connection methods lead to deformation and failure in the transition zone. An analysis of scientific and technical literature reveals the absence of a comprehensive approach to solving this issue. Current theoretical studies examine only isolated aspects of drafting device operation without accounting for their interactions. This results in an incomplete understanding of the processes occurring within the corrugated cylinder system and, consequently, hinders the optimization of their performance.